Comparative transcriptome analysis highlights the crucial roles of photosynthetic system in drought stress adaptation in upland rice - Zhang, Zheng-Feng; Li, Yuan-Yuan; Xiao, Ben-Ze (Scientific reports, 2016)
Drought stress is one of the major adverse environmental factors reducing plant growth. With the aim to elucidate the underlying molecular basis of rice response to drought stress, comparative transcriptome analysis was conducted between drought susceptible rice cultivar Zhenshan97 and tolerant cultivar IRAT109 at the seedling stage. 436 genes showed differential expression and mainly enriched in the Gene Ontology (GO) terms of stress defence. A large number of variations exist between these two genotypes including 2564 high-quality insertion and deletions (INDELs) and 70,264 single nucleotide polymorphism (SNPs). 1041 orthologous gene pairs show the ratio of nonsynonymous nucleotide substitution rate to synonymous nucleotide substitutions rate (Ka/Ks) larger than 1.5, indicating the rapid adaptation to different environments during domestication. GO and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of positive selection genes suggested that photosynthesis represents the most significant category. The collocation of positively selected genes with the QTLs of photosynthesis and the different photosynthesis performance of these two cultivars further illuminate the crucial function of photosynthesis in rice adaptation to drought stress. Our results also provide fruitful functional markers and candidate genes for future genetic research and improvement of drought tolerance in rice.